Self-adaptive Decomposition Level De-noising Method Based on Wavelet Transform - Jianzhao Huang; Jian Xie; Hongcai Li; Gui Tian; Xiaobo Chen (Institute of Advanced Engineering and Science, 2012)
In the threshold de-noising method based on wavelet transform, not only the threshold and threshold function, but also the decomposition level is an important factor in practical application. Signals under different noise levels correspond with different optimal decomposition levels. A method to determine the optimal decomposition level based on the white noise verification of wavelet detail coefficients is proposed. The effectiveness of this method is validated by the pressure signal de-noising experiment. Aiming to the need of sample points in hypothesis test, the performance of five hypothesis test methods are simulated and analyzed, and the application rules are summarized.DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1366